Antinociceptive Activity of Aqueous Fraction of Kratom Leaves Mitragyna speciosa Korth.) on Male Swiss Albino Mice - Widia Indri Nugraha; Robiyanto Robiyanto; Sri Luliana (Majalah Obat Tradisional, 2018)
Kratom (Mitragyna speciosa Korth.) has been known to have an analgesic opioid effect (antinociceptive). The major compound of kratom leaf is mitraginin, which has strong affinity on opioid receptor. The aim of this research is to prove antinociceptive effect of aqueous fraction of kratom leaf and its effective dose. The simplicia of kratom leaf was extracted with methanol 96%. Methanol extract fractioned with n-hexane, dichloromethane, ethyl acetate, and aquadest. This research used hot plate method on male Swiss Albino mice. The subject divided to 5 groups, negative control group, morphine 5,46 mg/kgBW, aqueous fraction 140, 240 and 560 mg/kgBW. Latency time was measured every 15 minutes over 2 hours period. Analytic statistical of latency time using One Way ANOVA shows that the aqueous fraction at the dose of 140, 280 and 560 mg/kgBW significantly differentiate with negative control group and positive control group. The antinociceptive effect increases with increasing doses. The three doses showed that the antinociceptive effect was no better than the positive control (Morphine)